Improvement in postoperative pain control by combined use of intravenous dexamethasone with dexmedetomidine after erector spinae plane block and serratus anterior plane block for thoracoscopic surgery: a randomized controlled trial - Li Zhang; Zhibiao Xu; Yuyun Liu; Zijie Ling; Sumin Yuan; Yuxiang Meng; Ziwei Li; Shoujie Feng; Su Liu; Linlin Zhao (BMC Anesthesiology)
Abstract Background Acute pain after thoracoscopic surgery is very noticeable and often requires additional techniques or adjunctive medications to reduce it. We investigated whether intravenous dexamethasone with dexmedetomidine after erector spinae plane block and serratus anterior plane block could further decrease the incidence of moderate-to-severe pain. Methods A total of 81 patients were randomly assigned to group C (20 mL normal saline), group S (10 mg dexamethasone + normal saline to 20 mL), or group SM (10 mg dexamethasone + 1 µg/kg dexmedetomidine + normal saline to 20 mL). All patients underwent erector spinae plane block and serratus anterior plane block 30 min before anesthesia induction and all drugs were infused intravenously 30 min after general anesthesia induction. The primary outcome was incidence of moderate-to-severe pain at 24 h on movement postoperatively. Secondary outcomes included incidence of moderate-to-severe pain on movement and at rest throughout the first two postoperative days, pain score, opioid consumption, quality of recovery and adverse effects. Results Group SM lowered the incidence of moderate-to-severe pain on movement at 24 h postoperatively than group C (11.1% vs. 48.0%; RR 0.231; 95% CI, 0.074 to 0.725) and group S (11.1% vs. 38.5%; RR 0.289; 95% CI, 0.089 to 0.933). Group SM reduced NRS score on movement (3.0 [3.0] vs. 3.0 [2.0] vs. 3.0[1.0]; P < 0.001) and total opioid consumption (26.0 [6.0] vs. 32.0 [9.0] vs. 28.0 [2.5]; P = 0.004) within 24 h after surgery, fewer patients required rescue analgesia (11.1% vs. 48.0% vs. 38.5%; P = 0.009). Group SM also lowered incidence of nausea and vomiting (7.4% vs. 32.0% vs. 30.8%; P = 0.047) and had a higher QoR-15 score at postoperative 24 h (132.0 [10.0] vs. 123.0 [8.0] vs. 127.5 [10.8]; P < 0.001). Conclusions Intravenous administration of dexamethasone with dexmedetomidine after erector spinae plane block and serratus anterior plane block further decreased the incidence of moderate-to-severe pain. It also reduced NRS scores and opioid consumption, making the postoperative pain control better for thoracoscopic surgery. Trial registration The study was registered at Chictr.org.cn with the number ChiCTR2400084435 on 05/16/2024.